Development of Communication Pondok Pesantren Darul Musyawarah Klumosari Banjaragung Bangsri - Nurul Huda; Siti Asiyah (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
The development of communication is able to change the form of communication in boarding school. The development of the communication of Pesantren into a theme that needs to be examined because of the uniqueness and cultural peculiarities that exist in the pesantren usually difficult to receive the presence of development and progress of communication media. This type of research is a qualitative descriptive with a historical and phenomenological approach by analyzing the progress of communication that occurred in the Islamic boarding school. The results of this study showed that the development of communication in Pondok Pesantren Darul Musyawarah is characterized by the development phase of human communication that is in the area of Pesantren is started from the development of communication through writing media, print media, contemporary telecommunications media, and online media as a means of communication and information Pesantren. The development of communication in Pondok Pesantren Darul Musyawarah not only occurs in internal boarding but the communication between personal and group communication both the surrounding community, government, and other outside networks.